Імплементація дромонічних мотивів у «Спогадах…» Г. Жевуського - Кацемба, Юліана; Katsemba, Yuliana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Висвітлено смислові аспекти та семантика дромонічих мотивів у «Спогадах ясновельможного пана Северина Соплиці, парнавського чашника» Г. Жевуського. Визначено центральні інваріанти мотиву дороги, які набувають сюжетотвірної, іманентної та концептуальної ролі в організації тексту: паломництво, роздоріжжя, втеча, повернення./ The problem of textual “motivation” of motives in the literary heritage of H. Rzewuski despite its plotmaking role, immanent and contextual significance in organization of aesthetic functioning of the text, less of researching like all the creations of famous Polish writer from Chudnov. The motif of a road is not major in the text of “Memories…”, but it has a lot of functions in the text organization because of narrative polyphony of the creation, in which a road is like a background of certain event, and like an intention motion in space, and like national comprehension of space. The central invariants of the road motif are pilgrimage, crossroads, escape, return. The conceptual role in the organization of the work of art gains a romantic motif of Soplitsa escape from reality in the world of memories. In its chronotope the memories of a narrator relate Rzeczpospolita of XVII–XVIII centuries and have the aim of gentry apology. The following dromonic motives concern on particular characters and plots, sometimes the narrator, associated with the motif of sin, moral decline, conscience and atonement. The conceptual motif of the escape from the reality echoes of plotmaking ones – escape from punishment and conviction. Pilgrimage to H. Rzewuski is not a unidirectional journey like in the traditional pilgrims prose, but always includes the return (happy or unhappy). This approach to representation of peregrination is interpreted intentionally: the road to the holy places is the way that the gavend’s characters overcome for atonement and the return road is represented like a God’s answer. The folklore motif of a hero on a crossroads based on an immanent consequences of choice: right and wrong from which the result of travel will depend on.
Implementation Reasons of Road in “Memories...” of H. Rzewuski.
Кацемба Ю. Імплементація дромонічних мотивів у «Спогадах…» Г. Жевуського / Юліана Кацемба // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 54-60.
Keywords: Генріх Жевуський; «Спогади ясновельможного пана Северина Соплиці»; романтизм; польська література; польськомовна література Правобережної України; мемуаристика; ґавенда; дромонічні мотиви; Henryk Rzewuski; “The Memories of great genry Severyn Soplitsa, a parnavsky partial”; romanticism; polish literature of the right bank Ukraine; memoirs; a gavenda; dromonic motives